The hidden admission agendas in Finnish primary teacher education in the 1990s, 2000s and 2010s. Issue 1 (2nd January 2023) - Mankki, Ville; Räihä, Pekka
ABSTRACT: Applicants' suitability for the teaching profession has been underlined in admissions to Finnish primary teacher education. Nevertheless, hidden agendas beyond teacher competence frameworks and attribute definitions have also influenced primary teacher admissions, particularly in the last three decades (the 1990s, 2000s and 2010s). This article investigates these agendas connected with the gender and age distribution of the admitted students, and illustrates how these agendas have led to admission reforms, the outcomes of which have usually been insufficient, unpredictable or even undesirable. It provides reinvigoration for the historical research of teacher education policy trends, insights into the gender segregation and age segregation of model citizenship and a more explicit articulation of the aims and visions of teacher education programmes in Finland.